Digital Sufism for Mental Resilience in the AI Era - Dimyati Sajari; Abdul Haris; Rasi’in Rasi’in; Raswan Raswan (ISLAMIKA, 2026)
The accelerating dominance of artificial intelligence (AI) and digital technologies has profoundly reshaped human cognition, emotion, and moral sensibility, while also generating new forms of psychological fragmentation and spiritual detachment. This study introduces Digital Sufism as a spiritually grounded and philosophically integrative framework for restoring inner equilibrium and sacred awareness in the digital era. Using a qualitative philosophical approach, the study synthesizes recent scholarship published between 2018 and 2024 on AI, mental health, and digital ethics with textual analysis of classical Sufi works, particularly al-Risālah al-Qushayrīyah by al-Qushayrī and Iḥyāʾ ʿUlūm al-Dīn by al-Ghazālī. The analysis examines how tazkiyat al-nafs (purification of the soul), murāqabah (divine mindfulness), and muḥāsabah (ethical self-reflection) can be reinterpreted as moral and psychological principles for AI design and digital conduct. The findings indicate that Sufism offers not only ethical direction but also existential resilience amid the algorithmic mediation of human life. By incorporating Sufi epistemology into digital environments, Digital Sufism fosters self-awareness, moral accountability, and transcendental consciousness as foundations for spiritually responsive technology. This study contributes to the formulation of a theoretical foundation for Digital Sufism as a contemporary articulation of Islamic mysticism that bridges spirituality, psychology, and digital ethics to promote holistic human development.